Discourse particles in the left periphery - Zimmermann, Malte (ZAS Papers in Linguistics, 2004)
This article analyses the German discourse particle wohl 'I suppose', 'presumably' as a syntactic and semantic modifier of the sentence types declarative and interrogative. It is shown that wohl does not contribute to the propositional, i.e. descriptive content of an utterance. Nor does it trigger an implicature. The proposed analysis captures the semantic behaviour of wohl by assuming that it moves to SpecForceP at LF, from where it can modify the sentence type operators in Force0 in compositional fashion. Semantically, a modification with wohl results in a weaker commitment to the proposition expressed in declaratives and in a request for a weaker commitment concerning the questioned proposition in interrogatives. Cross-linguistic evidence for a left-peripheral position of wohl (at LF) comes from languages in which the counterpart of wohl occurs in the clausal periphery overtly. Overall, the analysis sheds more light on the semantic properties of the left periphery, in particular of the functional projection ForceP.